The development of digital tools to assess and enhance the ethic children development in early childhood development centers - Govittayangkull, Pratana; Phutthima, Benjamas; Muangmool, Somchai (Asian Journal of Education and Training, 2023)
The research aimed to study the effects of digital tools on ethnic children in child development centers from four districts of Lamphun Province, Thailand. The samples were teachers, parents and health promoting hospital staff from the early childhood development centers 57 people in total from cluster sampling and randomized pretest-post-test control group design. The research instruments were interviewing form, focus group discussion recording form, questionnaire, and child development evaluation form. All digital tool assessment items were qualified with higher accuracy than the specified criterion of 0.50. Its correlation coefficient was higher than 0.85 at 0.05 significantly level. Conditions and needs for context analysis of digital tools had been conducted to develop and use it for evaluating the development of ethnic children in the centers. The data were analyzed using descriptive statistics and T-test. The results revealed that the digital tools compared with documents was different in use between the experimental and the control group of the study with statistically significant at 0.05 and teachers’ satisfactions of using the digital tools were also in high level. The study outcomes demonstrated that the development of digital tools in early childhood could enhance the ethical development of young children and provide educators and parents with valuable insights into a child's progress.